Cultural Nursing Competence Among Graduate Nurses From Selected University in Indonesia: Findings From The Nurses Cultural Competence Scale - Rafaelino Raditya A. N; Jesshica Wahyuningrum; Febi Muliani Ranawijaya; Juhdeliena Juhdeliena; Agustina Saputri (CV. Inara, 2026)
Cultural diversity in Indonesia poses significant challenges and opportunities in nursing practice. Nurses are required to provide culturally sensitive care to meet patients’ diverse cultural values, beliefs, and practices. Cultural care competence is therefore essential as a foundation for effective and patient-centered nursing care. However, evidence related to cultural competence among graduate nurses in Indonesia remains limited. This study employed a quantitative, descriptive, and analytical design with a cross-sectional approach. A total of 292 nurses who graduated from a selected University in Indonesia participated in the study using purposive sampling. Data were collected between March and April 2024 using the Nurses' Cultural Competence Scale (NCCS), which consists of 41 items covering four dimensions: cultural awareness, cultural knowledge, cultural sensitivity, and cultural skills. The data were analyzed using univariate descriptive statistics. The findings showed that 51.4% of respondents had a high level of cultural competence. Most participants were female (80.1%), with a mean age of 23.89 years and a mean working experience of 23.21 months. High levels were observed across all NCCS dimensions, including cultural awareness (54.1%), cultural knowledge (56.2%), cultural sensitivity (51%), and cultural skills (54.5%). The dominance of high cultural competence suggests that nurses possess adequate readiness to deliver culturally sensitive nursing care. Demographic characteristics such as age, gender, educational background, and early clinical exposure may have contributed to the development of cultural competence among respondents. The study demonstrates that nurses who graduated from a selected university generally exhibit good cultural care competence, which is crucial for providing responsive and culturally appropriate nursing care.